Optimization of structural parameters on hollow spherical cells manufactured by Fused Deposition Modeling (FDM) using Taguchi method. Issue 1 (January 2022) - Ali, Naserddine Ben; Khlif, Mohamed; Hammami, Dorra; Bradai, Chedly
There is a growing need for 3D printing of polymer structures in a cost-effective way and green. This study presents an experimental approach to investigate structural parameters effects on mechanical properties of polylactic acid (PLA) hollow-sphere structures manufactured with fused deposition modeling (FDM). The mechanical behavior characteristics of square_hexagonal stacking, closed_open porosity and parallel_perpendicular compression direction compared to the direction of manufacture under quasi-static uniaxial compression are examined using Taguchi method. The S/N ratio analysis and the Analysis of Variance (ANOVA) were used to find the optimal parameters that improve the mechanical properties (Young modulus, yield strength) and to provide a significant ranking of the different parameters analyzed in this paper. It was found that the optimum level and significance of each process parameter vary for "hexagonal cells, " "open porosity" and "parallel direction." The optimal values of the results give a Young modulus E of 90.12 MPa and a yield strengthσ y of 3 MPa. Furthermore, the experimental results further reveal that the porous structure with the loading direction that is parallel to the direction of manufacture, has a higher strength and a progressive collapse of the cells to those with a perpendicular direction.